Global Ibsen performing multiple modernities - Fischer-Lichte, Erika; Gronau, Barbara; Weiler, Christel (Routledge advances in theatre and performance studies, 2011)
'Global Ibsen' the different ways in which Ibsen's plays were & are performed in different cultures on five continents & examines the impact of such performances on the theatre, social life & politics of these cultures. It shows that performing Ibsen means performing multiple modernities.